Manual of References, Creating Tables and Figures in Scholarly Publications: APA 6 Rules - Mehmet Ali Akkaya (Türk Kütüphaneciliği)
One precondition of contribution of a discipline to its field, to the scientific word in general and to the entire humankind is producing qualified scientific publications in the related field or discipline. National and international standard(s) provided for citing and referencing tables and figures, in addition to the content (and context) of the scientific publications might provide the relevant publication to be more widely and correctly read and reviewed. This study deals with adaptation of the latest edition of the American Psychological Association (APA) rules. This book, where the APA rules -already a universal authority in citing and referencing- are enriched with specific examples for every type of information source, is a basic reference source after Prof. Dr. S. Kurbanoğlu’s “Kaynak Gösterme El Kitabı” (Referencing Handbook) in 2004 that can be implemented not only to the Information and Records Management field, but to the whole scientific world. The meaning and importance of the work of Şencan and Doğan, is much more profound in our country where along with the quality of the scientific publications, the stylistic compatibility with the scientific criteria is also very often questioned.